A Neglected Opportunity: Entrepreneurship Education in the Lower High School Curricula for Technology in South Africa and Botswana. Issue 1 (2nd January 2018) - du Toit, Adri; Gaotlhobogwe, Mike
Abstract : Technology is a school subject that forms part of the compulsory curriculum for high school learners in South Africa, and is a core theme in the subject Design and Technology in Botswana high schools. Knowledge and production skills acquired in the subject are applied to solve real-life problems consistent with the steps of the design process. The simultaneous development of learners' problem-solving and production skills in the subject suggests that Technology could play a vital role in preparing learners as entrepreneurs. Such learning could result in innovation or the manufacture of income-generating products. In these two countries, where youth unemployment is a constant challenge, developing such skills as part of learners' school curriculum may contribute to alleviating the unemployment levels of young people. For any subject to effectively support entrepreneurship, however, its curriculum should be designed to sustain such development. A structured qualitative curriculum analysis was used to investigate if and how entrepreneurship is included in the Technology curricula at lower high school levels in South Africa and Botswana. The study found that, although Technology has great potential to support and develop entrepreneurship, the curricula investigated do not include explicit entrepreneurship content, nor pedagogical guidance to support teachers in this regard. The opportunity that Technology offers to contribute to reducing youth unemployment is therefore neglected in these curricula. Recommendations for the strengthening of entrepreneurship education in both curricula were made, with the anticipation that implementation of recommended improvements could contribute to the alleviation of youth unemployment in both countries.